Risk assessment terminology: risk communication part 2 - Gaetano Liuzzo; Stefano Bentley; Federica Giacometti; Silvia Piva; Andrea Serraino (Italian Journal of Food Safety, 2016)
The paper describes the terminology of risk communication in the view of food safety: different aspects of risk perception (perceived risk, media triggers, the psychometric paradigm, fright factors and cultural determinants of risk perception) are described. The risk profile elements are illustrated in the manuscript: hazard-food commodity combination(s) of concern; description of the public health problem; food production, processing, distribution and consumption; needs and questions for the risk assessors; available information and major knowledge gaps and other risk profile elements.